Morning glory [videorecording (DVD)] - Michell, Roger, 1956-; McAdams, Rachel, 1978-; Ford, Harrison, 1942-; Keaton, Diane; Wilson, Patrick, 1973- (Paramount Home Entertainment, 2011)
For Becky, running a TV show in New York City was the big break she dreamed of, until star co-anchors Mike and Colleen declare an all-out, on-air war. Making the show work with its cast of eccentric characters and outrageous story angles will take a major miracle, but Becky is ready to rise and outshine.